Spectrophotometric Determination of Micro Amounts of Gold(III) Using Cyclopentane-spiro-2´ -(1-Methyl-2´ ,4´ -Dithio)-s-Triazine - Chavan, J.D.; Joshi, V.P. (Asian Journal of Chemistry, 2010)
Gold(III) forms an intense yellow soluble complex with cyclopentane-spiro-2´, (1-methyl-2´ ,4´ -dithio )-s triazine (CPSMDTT) in acidic medium. The complex gives maximum absorption at 435nm in the pH range 3.8 to 4.0. Beer's law is obeyed over the range 1 to 7 ppm of Au(III). The molar absorptivity and Sandell's sensitivity of the complex are 1.28 x 104 dm3 mol–1 cm–1 and 0.015 μg cm–2, respectively. Standard deviation is evaluated to be 0.69. The composition of the complex is established by Job's method and mole ratio method as 1 : 3, (Au(III): CPSMDTT). The effect of various diverse ions is also studied.